Comparison of umbilical venous and intraosseous access during simulated neonatal resuscitation - Rajani, Anand K; Chitkara, Ritu; Oehlert, John; Halamek, Louis P (Pediatrics (Evanston), 2011)
Emergent umbilical venous catheter (UVC) placement for persistent bradycardia in the delivery room is a rare occurrence that requires significant skill and involves space constraints. Placement of an intraosseous needle (ION) in neonates has been well described. The ION is already used in the pediatric population and is placed at an anatomic location distant from where chest compressions are performed. In this study we compared time to placement, errors in placement, and perceived ease of use for UVCs and IONs in a simulated delivery room. Forty health care providers were recruited. Subjects were shown an instructional video of both techniques and allowed to practice placement. Subjects participated in 2 simulated neonatal resuscitations requiring intravenous epinephrine. In 1 scenario they were required to place a UVC and in the other an ION. Scenarios were recorded for later analysis of placement time and error rate. Subjects were surveyed regarding the perceived level of difficulty of each technique. The average time required for ION placement was 46 seconds faster than for UVC placement (P < .001). There was no significant difference in the number of errors between UVC and ION placement or in perceived ease of use. In a simulated delivery room setting, ION placement can be performed more quickly than UVC insertion without any difference in technical error rate or perceived ease of use. ION insertion should be considered when rapid intravenous access is required in the neonate at the time of birth, especially by health care professionals who do not routinely place UVCs.